2013
DOI: 10.1186/1471-2253-13-41
|View full text |Cite
|
Sign up to set email alerts
|

The increase of vasomotor tone avoids the ability of the dynamic preload indicators to estimate fluid responsiveness

Abstract: BackgroundThe use of vasoconstrictor can affect the dynamic indices to predict fluid responsiveness. We investigate the effects of an increase of vascular tone on dynamic variables of fluid responsiveness in a rabbit model of hemorrhage, and to examine the ability of the arterial pressure surrogates dynamic indices to track systolic volume variation (SVV) during hypovolemia under increased vasomotor tone.MethodsEighteen anesthetized and mechanically ventilated rabbits were studied during normovolemia (BL) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 39 publications
0
24
0
1
Order By: Relevance
“…3,16 Moreover, no study has demonstrated an association between CO and Ea dyn . 3,4,13,14 We found a weak association between Ea dyn and CO TTE probably related to the HR dependence of CO. As expected, we did not find any association with SV, which represents a flow factor independent of HR.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…3,16 Moreover, no study has demonstrated an association between CO and Ea dyn . 3,4,13,14 We found a weak association between Ea dyn and CO TTE probably related to the HR dependence of CO. As expected, we did not find any association with SV, which represents a flow factor independent of HR.…”
Section: Discussionmentioning
confidence: 57%
“…14e16 In studies assessing the effect of vasopressors, Ea dyn was demonstrated to change while CO did not change. 3,4,14 Ea dyn was demonstrated to be associated to cardiac factors (HR and peak of velocity of aortic blood flow) and vascular factors (arterial compliance and vascular resistance). 3,16 Moreover, no study has demonstrated an association between CO and Ea dyn .…”
Section: Discussionmentioning
confidence: 99%
“…19) High variability of SV indicates the presence of hypovolemia at a steady vascular tone, whereas vasodilators have been shown to increase SVV at constant body fluid. 20) The strong correlation between peaks of the Pd/Pa ratio and SVV observed in this The Pd/Pa ratio at maximal hyperemia is affected by the degree of stenosis, whereas the positions of SVV peaks are influenced by vascular tone and preload. This precludes direct evaluation of the relations between these two parameters.…”
Section: Discussionmentioning
confidence: 64%
“…However, in a rabbit hemorrhage model, we have shown that PHE infusion (15 mcg/kg/min) induced a decrease in aortic flow with a significant SV decrease after BW compared with normovolemia. The different hemodynamic response to PHE may be probably related to the different doses of the α-adrenergic agonist (small boluses vs. relatively large continuous doses) 11,20 . We propose that PHE infusion had a predominant effect on the Rv (decreased slope of the VR curve without a change of MCFP), which tends to decrease VR.…”
Section: Discussionmentioning
confidence: 99%